Five decades of strong temporal variability in the flow of Brunt Ice Shelf, Antarctica - Gudmundsson, Hilmar; de Rydt, Jan; Nagler, Thomas (Journal of Glaciology, 2017)
Data showing velocity changes on the Brunt Ice Shelf (BIS), Antarctica, over the last 55 years are presented and analysed. During this period no large-scale calving events took place and the ice shelf gradually grew in size. Ice flow velocities, however, fluctuated greatly, increasing twofold between 1970 and 2000, then decreasing again to previous levels by 2012 after which velocities started to increase yet again. In the observational period, velocity changes in the order of 10% a−1 have commonly been observed, and currently velocities are increasing at this rate. By modelling the ice flow numerically, we explore potential causes for the observed changes in velocity. We find that a loss of mechanical contact between the BIS and the McDonald Ice Rumples following a local calving event in 1971 would explain both the increase and the subsequent decrease in ice velocities. Other explanations involving enlargement of observed rift structures are discounted as the effects on ice flow are found to be too small and the spatial pattern of velocity change inconsistent with data. The most recent phase of acceleration remains unexplained but may potentially be related to a recent re-activation of a known rift structure within the BIS.